2020
DOI: 10.32707/ercivet.828319
|View full text |Cite
|
Sign up to set email alerts
|

Bazı Bitkisel Yağların Zebra Balıklarında Anestezik Rolü

Abstract: Anesthetics have been important in ornamental fishes for transport and restriction of behaviors as well as for surgical applications and studies in science. Also, more economical and appropriate anesthetics can be common choice for these stiuations. In the study, a total of two hundred and fifty two zebrafish (forty two females and forty two males in each group) divided in three groups were studied as group A (Anise oil); group T (Thyme oil); group M (Mint oil). Anesthesia intake and lethal dose values were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For this reason, it has been observed that anise is not suitable for anaesthesia in carp. Similarly, Seyidoglu and Yagcılar ( 2020 ) reported that anise at concentrations of 0.1–30 mg L −1 did not show an anaesthetic effect and caused mortality in zebrafish.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…For this reason, it has been observed that anise is not suitable for anaesthesia in carp. Similarly, Seyidoglu and Yagcılar ( 2020 ) reported that anise at concentrations of 0.1–30 mg L −1 did not show an anaesthetic effect and caused mortality in zebrafish.…”
Section: Discussionmentioning
confidence: 87%
“…In the selection criteria of anaesthetics, induction and recovery time of anaesthesia are important (Martins et al 2019 ). Anaesthetics should be effective in low concentrations and have no toxic effect on fish (Seyidoglu and Yagcılar 2020 ). Therefore, the search for natural anaesthetic agents that are reliable and effective in fish has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And different nanoformulations of EOs extracted from Alpinia galanga and Aeollanthus suaveolens were also evaluated for organ distribution properties and anesthetic activity in zebrafish using comparable techniques and indicators (de Oliveira Ferraz et al, 2020;Khumpirapang et al, 2021). Furthermore, recovery time served as a crucial metric for assessing the anesthetic efficacy of various EOs such as anise oil, thyme oil, and mint oil (Seyidoglu and Yagcilar, 2020), and EOs derived from Cuminum cyminum (Khosravanizadeh et al, 2020), Acmella oleracea, Piper alatabaccum (Leite et al, 2022). Greater amounts of serum could be collected and lower serum levels of cortisol were present in fish euthanized with clove oil (0.1%) compared with an equipotent dose of MS222 (7.8 mM).…”
Section: Zebrafish Models For the Evaluation Of Anesthetic Activitymentioning
confidence: 99%